2012
DOI: 10.1074/jbc.c111.325795
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of tRNA Synthetase Active Sites for Chemical Fidelity

Abstract: Background: Mycoplasma mobile leucyl-tRNA synthetase has lost its CP1 domain via reductive genome evolution resulting in impaired editing. Results: Fusion of cognate and noncognate bacterial CP1 domains to the aminoacylation canonical core enhances fidelity. Conclusion: CP1 domain insertions influence amino acid discrimination in the synthetic site. Significance: Evolutionary addition of the CP1 domain confers multiple mechanisms to achieve fidelity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 41 publications
3
14
0
Order By: Relevance
“…Our recent work revealed that fusion of the CP1 domains to M. mobile LeuRS can improve amino acid selectivity for aminoacylation (30 conformation more suitable for pretransfer editing and amino acid selection. In many cases, this activity seems to be enhanced in the presence of tRNA (20,21,23).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our recent work revealed that fusion of the CP1 domains to M. mobile LeuRS can improve amino acid selectivity for aminoacylation (30 conformation more suitable for pretransfer editing and amino acid selection. In many cases, this activity seems to be enhanced in the presence of tRNA (20,21,23).…”
Section: Discussionmentioning
confidence: 99%
“…As such, the CP1 domain from E. coli LeuRS was fused to M. mobile LeuRS (MmLeuRS/CP1 Leu ) (30). We also constructed hybrids using the CP1 domains from IleRS (MmLeuRS/CP1 Ile ) and ValRS (MmLeuRS/CP1 Val ) (30). Each of the hybrid LeuRSs displayed leucylation activities comparable to the wild-type M. mobile enzyme (30) (Fig.…”
Section: X-ray Crystal Structure Of M Mobile Leurs-leuams Is Similar Tomentioning
confidence: 99%
See 3 more Smart Citations